In Vitro Assessment of Early Bacterial Activity on Micro/Nanostructured Ti6Al4V Surfaces - Valdez-Salas, Benjamin (Molecules, 2017)
It is imperative to understand and systematically compare the initial interactions between bacteria genre and surface properties. Thus, we fabricated a flat, anodized with 80 nm TiO(2) nanotubes (NTs), and a rough Ti6Al4V surface. The materials were characterized using field-emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDX) and atomic force microscopy (AFM). We cultured in vitro Staphylococcus epidermidis (S. epidermidis) and Pseudomonas aeruginosa (P. aeruginosa) to evaluate the bacterial-surface behavior by FE-SEM and viability calculation. In addition, the initial effects of human osteoblasts were tested on the materials. Gram-negative bacteria showed promoted adherence and viability over the flat and rough surface, while NTs displayed opposite activity with altered morphology. Gram-positive bacteria illustrated similar cellular architecture over the surfaces but with promoted surface adhesion bonds on the flat alloy. Rough surfaces supported S. epidermidis viability, whilst NTs exhibited lower vitality. NTs advocated promoted better osteoblast organization with enhanced vitality. Gram-positive bacteria suggested preferred adhesion capability over flat and carbon-rich surfaces. Gram-negative bacteria were strongly disturbed by NTs but largely stimulated by flat and rough materials. Our work proposed that the chemical profile of the material surface and the bacterial cell wall characteristics might play an important role in the bacteria-surface interactions.